Implementasi Aplikasi al-Kafâlah di Lembaga Keuangan Syari’ah di Indonesia - Moh. Asra (Program Pascasarjana Universitas Ibrahimy, 2020)
Generally, al-kafalah is an act of combining the dependents of the insurer and the main insurer related to claims about life, debt, goods, or work. Al-kafalah is implemented by the existence of the insurer, the main insurer, the insured, and the dependents. This research primary source is literature, using a qualitative descriptive approach. Shaykh Mustofa Al-Khin and Shaykh Mustofa Al-Bugha quote the wisdom of al-kafalah through the maqashid syariah. He both explained that the al-kafalah procedure made it easier for someone to meet their needs through the principle of helping. Al-kafalah can protect the possibilities that occur during the transaction or as long as the debt has not been paid. Al-kafalah has been widely applied in financial institutions such as banks, as well as e-commerce based on the al-kafalah bi al-ujrah system which has previously been permitted by contemporary scholars. Meanwhile, al-kafalah which is based on tabarru 'in Indonesia is only found in the Indonesian Health Card (KIS) mechanism.